Privatized corrections in the 21st century - Montes, Andrea N. (Criminology & public policy, 2019)
Governments historically have relied on private organizations to assist with the provision of correctional punishment and services. This reliance continues but has engendered considerable debate that stems from ideological divides. Debate stems as well from a disjuncture between the limited evidence about privatization and calls for evidence‐based policy. In this article, we present a conceptual framework for identifying what is and is not known about privatization and for guiding scholarship and policy. We then discuss key issues that must be addressed to advance knowledge about privatization and productively inform policy debates.